Notes on Alliteration in the Poetic Edda - Shimomiya, Tadao (Lingua Posnaniensis, 2011)
The Berlin Anglicist and linguist Martin Lehnert (1955: 33) says that there are some 30,000 alliterative lines in Old English, 7,300 Eddic long lines, 6,000 and 335 in Old Saxon (Heliand and Genesis) and 200 in Old High German (Hildebrandslied, Muspilli etc.). The following contains some notes on alliteration in the Poetic Edda. The three main types of alliteration ([a] for alliterating, [x] for not alliterating stave) are [aa/ax] [ax/ax] and [xa/ax]. There are, however, a number of cases where the principal stave (Hauptstab, hofuðstafr, Snorri Sturluson, c.1220, quoted from A. Heusler 1918-1919, §35) is not in the normal place. Moreover, there are also several lines where no alliteration is available, and where, although I am not a medieval Icelandic poet, I would compose the line to make it more alliterative. Toward the end of the article is given a select list of 50 alphabetically arranged alliterations from the Poetic Edda.